First Focal Mechanisms of Marsquakes. Issue 4 (19th April 2021) - Brinkman, Nienke; Stähler, Simon C.; Giardini, Domenico; Schmelzbach, Cédric; Khan, Amir; Jacob, Alice; Fuji, Nobuaki; Perrin, Clement; Lognonné, Philippe; Beucler, Eric; Böse, Maren; Ceylan, Savas; et al.
Abstract: Since February 2019, NASA's InSight lander is recording seismic signals on the planet Mars, which, for the first time, allows to observe ongoing tectonic processes with geophysical methods. A number of Marsquakes have been located in the Cerberus Fossae graben system in Elysium Planitia and further west, in the Orcus Patera depression. We present a first study of the focal mechanisms of three well‐recorded events (S0173a, S0183a, S0235b) to determine the processes dominating in the source region. We infer for all three events a predominantly extensional setting. Our method is adapted to the case of a single, multicomponent receiver and based on fitting waveforms of P and S waves against synthetic seismograms computed for the initial crustal velocity model derived by the InSight team. We explore the uncertainty due to the single‐station limitation and find that even data recorded by one station constrains the mechanisms (reasonably) well. For the events in the Cerberus Fossae region (S0173a, S0235b) normal faulting with a relatively steep dipping fault plane is inferred, suggesting an extensional regime mainly oriented E‐W to NE‐SW. The fault regime in the Orcus Patera region is not determined uniquely because only the P wave can be used for the source inversion. However, we find that the P and weak S waves of the S0183a event show similar polarities to the event S0173, which indicates similar fault regimes. Plain Language Summary: As time passes, the mysterious interior of Mars is slowly being unraveled due to the detection and analysis of Marsquakes recorded with a seismograph carried by the InSight lander. Close to 400 Marsquakes have so far been identified, yet only a handful of those show similarities to earthquakes. Those earth‐like events are located near the Cerberus Fossae and Orcus Patera regions. We take advantage of the similarity between Marsquakes and earthquakes and apply a methodology developed for earthquake characterization before seismic recorders became abundant on Earth. We find that the Marsquakes in these source regions are dominated by extensional rather than compressing features. This is important information to further understand what causes Marsquakes. Key Points: We infer the tectonic setting in Cerberus Fossae on Mars by seismic source inversion We present a robust inversion strategy for single‐station moment tensor inversion Three Marsquakes recorded by InSight reveal a predominantly normal faulting regime